Wireless performance evaluation for FCSIT labs - Aniza, Binti Yusup (Faculty of Computer Science and Information Technology., 2006)
There are lots of factor that can affect the performance of wireless network, such as the internal and external interference, user capacity and the application load itself. The focus of the project is to examine the effect of the various heavy application running on Wireless LAN clients in FCSIT lab to the wireless LAN through and the response time for Email, FTP and HTTP application. The project used OPNET Modeler Version 10.0 to stimulate the wireless network based on the existing network configuration in FCSIT Labs. The model must be closely similar to the real one and the challenge was to be able to make sure that the network configuration that are being modeled really match the existing one. There are five scenarios created for the project , each with different number of Access Point. The performance of the Wireless LAN found to have improved by adding more Access Point to the wireless network.